2020
DOI: 10.1016/j.ebiom.2020.102995
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering ventilator-associated pneumonia from a new dimension of the lung microbiome

Abstract: Complex microbial communities that reside in the lungs, skin and gut are now appreciated for their role in maintaining organ, tissue and immune homoeostasis. As lungs are currently seen as an ecosystem, the shift in paradigm calls for the consideration of new algorithms related to lung ecology in pulmonology. Evidence of lung microbiota does not solely challenge the traditional physiopathology of ventilator-associated pneumonia (VAP); indeed, it also reinforces the need to include molecular techniques in VAP d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 75 publications
3
17
0
1
Order By: Relevance
“…Similar disruptions in lung homoeostasis have been reported in patients with bacterial ventilator-associated pneumonia (Fernández-Barat et al 2020). Krause et al observed a decrease of fungal diversity in ventilated patient with pneumonia and an increase of Candida spp., representing 75% of fungal species (Krause et al 2016).…”
Section: Discussionsupporting
confidence: 79%
“…Similar disruptions in lung homoeostasis have been reported in patients with bacterial ventilator-associated pneumonia (Fernández-Barat et al 2020). Krause et al observed a decrease of fungal diversity in ventilated patient with pneumonia and an increase of Candida spp., representing 75% of fungal species (Krause et al 2016).…”
Section: Discussionsupporting
confidence: 79%
“…Of note, the disruption of microbial homeostasis might be associated with the occurrence of VAP. Indeed, orotracheal intubation, which might impair the natural lung defense mechanisms, is a promoter of microbiome dysbiosis [53]. Furthermore, the gut-lung-microbiome axis is one of current researching hotspots in basic research in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…It is anticipated that the results will reshape existing concepts and improve the clinical management of patients accordingly. 82,83 Longitudinal studies of the sputum microbiome in patients with BE 84 suggest that the management of chronic bronchial infection can be improved by therapy for its microbiome. This must consider the burden of the pathogen, the stability of the community, and the acute and chronic responses of the community to antibiotics.…”
Section: Respiratory Microbiome Dysbiosismentioning
confidence: 99%